Children's fear of needle injections: a qualitative study of training sessions for children with rheumatic diseases before home administration - Kari Sørensen; Helge Skirbekk; Gunnvald Kvarstein; Hilde Wøien (BMC, 2020)
Abstract Background Treatment of rheumatic diseases in children often includes long-term needle injections, which represent a risk for refusing medication based on potential needle-fear. How nurses manage children's fear and pain during the initial educational training session of subcutaneous injections, may affect the management of the subsequent injections in the home settings. The aim of this study was to explore how children expressed fear and pain during these training sessions, and how adults' communication affected children's expressed emotions. Methods This qualitative explorative study used video observations and short interviews during training sessions in a rheumatic hospital ward. Participants were children between five and fifteen years (n = 8), their parents (n = 11) and nurses (n = 7) in nine training sessions in total. The analysis followed descriptions of thematic analysis and interaction analysis. Results The children expressed fears indirectly as cues and nonverbal signs more often than direct statements. Three children stated explicit being afraid or wanting to stop. The children worried about needle-pain, but experienced the stinging pain after the injection more bothersome. The technical instructions were detailed and comprehensive and each nurse shaped the structure of the sessions. Both nurses and parents frequently offered coping strategies unclearly without sufficient time for children to understand. We identified three main adult communication approaches (acknowledging, ambiguous and disregarding) that influenced children's expressed emotions during the training session. Conclusions Children's expression of fear was likely to be indirectly, and pain was mostly related to the injection rather than the needle stick. When adults used an acknowledging communication and offered sufficient coping strategies, children seemed to become involved in the procedure and acted with confidence. The initial educational training session may have a great impact on long-term repeated injections in a home setting by providing children with confidence at the onset.